2021
DOI: 10.1093/restud/rdab051
|View full text |Cite
|
Sign up to set email alerts
|

Winning by Default: Why is There So Little Competition in Government Procurement?

Abstract: Government procurement contracts rarely have many bids, often only one. Motivated by the institutional features of federal procurement, this paper develops a principal-agent model where a buyer seeks sellers at a cost and negotiates contract terms with them. The model is identified and estimated with data on IT and telecommunications contracts. We find the benefits of drawing additional sellers are significantly reduced because the procurement agency can extract informational rents from sellers. Another factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…They find that increasing buyers' discretion on winner selection has a neutral and sometimes even positive effect on procurement outcomes, although it increases the chances of the same firms winning again. Kang and Miller (2022) observe little competition in US federal procurement auctions and, in line with Coviello et al (2017), find an increase in costs when public officials' discretion is reduced. Calzolari and Spagnolo (2009) provide a theoretical background to explain these empirical results.…”
Section: Literature Reviewmentioning
confidence: 63%
“…They find that increasing buyers' discretion on winner selection has a neutral and sometimes even positive effect on procurement outcomes, although it increases the chances of the same firms winning again. Kang and Miller (2022) observe little competition in US federal procurement auctions and, in line with Coviello et al (2017), find an increase in costs when public officials' discretion is reduced. Calzolari and Spagnolo (2009) provide a theoretical background to explain these empirical results.…”
Section: Literature Reviewmentioning
confidence: 63%
“…The substantial increase in cost, paired with relatively small delays, is explained by the cost‐plus nature of most of the contracts (79%). The preponderance of cost‐plus contracts in DoD procurement is well documented (Carril & Duggan, 2018; Kang & Miller, 2017). It is explained by the DoD's interest to obtain a timely completion of projects that have highly uncertain costs at the time of bidding 13 .…”
Section: Datamentioning
confidence: 99%
“…The data covers all federal contracting offices' transactions over $3000. They have been used extensively in previous research, including studies byLiebman and Mahoney (2017),Warren (2014),Kang and Miller (2017),Giuffrida and Rovigatti (2018),Decarolis et al (2021).10 The R&D code specified in each contract comes from the variable "Product or Service Code" and is composed of two alphabetic and two…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the construction of social housing in France, Chever, Saussier, and Yvrande-Billon (2017) found that negotiations after an informal auction led to lower costs than those following open auctions. Kang and Miller (2015) developed a procurement auction model in which the degree of competition is optimally chosen by public buyers, finding that limiting competition does not necessarily result in higher procurement costs.…”
mentioning
confidence: 99%